Optical metabolic imaging of treatment response in human head and neck squamous cell carcinoma. - Amy T Shah; Michelle Demory Beckler; Alex J Walsh; William P Jones; Paula R Pohlmann; Melissa C Skala (PLoS ONE)
Optical metabolic imaging measures fluorescence intensity and lifetimes from metabolic cofactors nicotinamide adenine dinucleotide (NADH) and flavin adenine dinucleotide (FAD). These molecular level measurements provide unique biomarkers for early cellular responses to cancer treatments. Head and neck squamous cell carcinoma (HNSCC) is an attractive target for optical imaging because of easy access to the site using fiber optic probes. Two HNSCC cell lines, SCC25 and SCC61, were treated with Cetuximab (anti-EGFR antibody), BGT226 (PI3K/mTOR inhibitor), or cisplatin (chemotherapy) for 24 hours. Results show increased redox ratio, NADH α1 (contribution from free NADH), and FAD α1 (contribution from protein-bound FAD) for malignant cells compared with the nonmalignant cell line OKF6 (p<0.05). In SCC25 and SCC61 cells, the redox ratio is unaffected by cetuximab treatment and decreases with BGT226 and cisplatin treatment (p<0.05), and these results agree with standard measurements of proliferation rates after treatment. For SCC25, NADH α1 is reduced with BGT226 and cisplatin treatment. For SCC61, NADH α1 is reduced with cetuximab, BGT226, and cisplatin treatment. Trends in NADH α1 are statistically similar to changes in standard measurements of glycolytic rates after treatment. FAD α1 is reduced with cisplatin treatment (p<0.05). These shifts in optical endpoints reflect early metabolic changes induced by drug treatment. Overall, these results indicate that optical metabolic imaging has potential to detect early response to cancer treatment in HNSCC, enabling optimal treatment regimens and improved patient outcomes.